RAB6 and dynein drive post‐Golgi apical transport to prevent neuronal progenitor delamination. (18th August 2022) - Brault, Jean‐Baptiste; Bardin, Sabine; Lampic, Marusa; Carpentieri, Jacopo A; Coquand, Laure; Penisson, Maxime; Lachuer, Hugo; Victoria, Guiliana Soraya; Baloul, Sarah; El Marjou, Fatima; Boncompain, Gaelle; Miserey‐Lenkei, Stephanie; et al.
Abstract: Radial glial (RG) cells are the neural stem cells of the developing neocortex. Apical RG (aRG) cells can delaminate to generate basal RG (bRG) cells, a cell type associated with human brain expansion. Here, we report that aRG delamination is regulated by the post‐Golgi secretory pathway. Using in situ subcellular live imaging, we show that post‐Golgi transport of RAB6+ vesicles occurs toward the minus ends of microtubules and depends on dynein. We demonstrate that the apical determinant Crumbs3 (CRB3) is also transported by dynein. Double knockout of RAB6A/A' and RAB6B impairs apical localization of CRB3 and induces a retraction of aRG cell apical process, leading to delamination and ectopic division. These defects are phenocopied by knockout of the dynein activator LIS1. Overall, our results identify a RAB6‐dynein‐LIS1 complex for Golgi to apical surface transport in aRG cells, and highlights the role of this pathway in the maintenance of neuroepithelial integrity. Synopsis: A RAB6‐Dynein‐LIS1 complex controls post‐Golgi apical transport of CRUMBS in neuronal progenitors. Impairment of this pathway alters apical junctions, causes delamination of these epithelial cells, and leads to the formation of basal progenitors. RAB6‐dynein‐LIS1 control post‐Golgi transport of CRUMBS to the apical surface of apical progenitors. This transport pathway is essential for the maintenance of apical junctions. Alteration of this transport pathway leads to the generation of basal progenitors. Abstract : A RAB6‐Dynein‐LIS1 complex controls post‐Golgi apical transport of CRUMBS in neuronal progenitors. Impairment of this pathway alters apical junctions, causes delamination of these epithelial cells, and leads to the formation of basal progenitors.